Kinetics of uranium(VI) lability and solubility in aerobic soils. (November 2020) - Izquierdo, M.; Young, S.D.; Bailey, E.H.; Crout, N.M.J.; Lofts, S.; Chenery, S.R.; Shaw, G.
Abstract: Uranium may pose a hazard to ecosystems and human health due to its chemotoxic and radiotoxic properties. The long half-life of many U isotopes and their ability to migrate raise concerns over disposal of radioactive wastes. This work examines the long-term U bioavailability in aerobic soils following direct deposition or transport to the surface and addresses two questions: (i) to what extent do soil properties control the kinetics of U speciation changes in soils and (ii) over what experimental timescales must U reaction kinetics be measured to reliably predict long-term of impact in the terrestrial environment? Soil microcosms spiked with soluble uranyl were incubated for 1.7 years. Changes in U VI fractionation were periodically monitored by soil extractions and isotopic dilution techniques, shedding light on the binding strength of uranyl onto the solid phase. Uranyl sorption was rapid and strongly buffered by soil Fe oxides, but U VI remained reversibly held and geochemically reactive. The pool of uranyl species able to replenish the soil solution through several equilibrium reactions is substantially larger than might be anticipated from typical chemical extractions and remarkably similar across different soils despite contrasting soil properties. Modelled kinetic parameters indicate that labile U VI declines very slowly, suggesting that the processes and transformations transferring uranyl to an intractable sink progress at a slow rate regardless of soil characteristics. This is of relevance in the context of radioecological assessments, given that soil solution is the key reservoir for plant uptake. Graphical abstract: Image 1 Highlights: Rapid initial loss of soluble uranyl is followed by a slow sorption process. Short-term experiments may not reliably predict long-term U solubility and K d . Uranyl ions are strongly adsorbed to soil Fe oxides through inner-sphere complexes. Adsorbed uranyl is largely reversibly held and biologically available. Labile U declines very slowly with no clear dependence on soil properties.